Surgical burn care in sub-Saharan Africa: A systematic review. Issue 4 (October 2019) - Botman, M.; Beijneveld, J.A.; Negenborn, V.L.; Hendriks, T.C.C.; Schoonmade, L.J.; Mackie, D.P.; van Zuijlen, P.P.M.
Abstract: Objective: Burn injuries are still one of the most common and devastating global health problems worldwide. The vast majority of burns occur in low- and middle-income countries, particularly in sub-Saharan Africa. A certain standard of surgical and anaesthesia care is essential to minimize morbidity and mortality. The aim of this study is to obtain baseline information on surgical burn care in sub-Saharan Africa and to determine how this can be improved. Methods: A systematic review (PRISMA) was conducted. Data was extracted regarding study characteristics, patient and burn characteristics (aetiology of burn, total body surface area (TBSA), depth of burn), wound treatment and surgical care (type of wound dressing, surgery rate, skin graft rate, early vs. delayed) and outcome (mortality, wound infection, take of the grafts, length of stay, contracture formation). Results: Forty-two studies from 12 different countries were included[1–42] . Most studies were case series (37). The mean TBSA was 17.3%. Of the included patients, 44.4% underwent some type of operation. Overall mortality was 13.1%. Only 13 studies reported on the number of patients with deep burn wounds in their population. In this group 89.4% was grafted, of which 25.4% was performed early (<10  days), 67.6% delayed and 7.0% not recorded. Conclusion: Research on surgical burn care in sub-Saharan Africa is scarce and the quality is poor. Future studies should ensure uniform data collection to enable comparison between treatment strategies. The International Society for Burn Injuries (ISBI) guidelines for burns, published in 2016, provide a practical tool, not only for daily practice but also for research on different treatment protocols.